Strengthening The Entrepreneurial Mentality Of Students Through Islamic Religious Education And Ethics At SMK Negeri 4 Malang And SMK PGRI 3 Malang - Qomaruddin Qomaruddin; Muhtadi Ridwan; Wahidmurni Ahmad Barizi (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This research aims to strengthen students' entrepreneurial mentality through Islamic Religious Education and Ethics (PAI-BP) at SMK Negeri 4 Malang and SMK PGRI 3 Malang. Strengthening the entrepreneurial mentality is very important considering the competency demands of vocational school graduates who must be able to compete in the era of digital technology and global competition. This study uses a qualitative approach with a multi-site case study design. Data collection is carried out through in-depth interviews, observations, and documentation. The study results show that strengthening the entrepreneurial mentality is carried out by preparing PAI-BP learning tools based on vision, mission, and collaborative projects and developing religious culture and Islamic extracurricular activities. Implementing the entrepreneurship mentality strengthening program includes innovative learning of PAI-BP inside and outside the classroom, spiritual and cultural activities, and collaboration with Islamic extracurricular activities. The conclusion of this study shows that strengthening students' entrepreneurial mentality through PAI-BP positively impacts students' attitudes, skills, and entrepreneurial mentality, including creativity, cooperation, confidence, and independence.